Impact of the generation of EGFR‐TKIs administered as prior therapy on the efficacy of osimertinib in patients with non‐small cell lung cancer harboring EGFR T790M mutation. Issue 3 (21st November 2020) - Miyashita, Yosuke; Ko, Ryo; Shimada, Naoko; Mitsuishi, Yoichiro; Miura, Keita; Matsumoto, Naohisa; Asao, Tetsuhiko; Shukuya, Takehito; Shibayama, Rina; Koyama, Ryo; Takahashi, Kazuhisa
Abstract: Background: There are few studies that directly compare the effects of osimertinib on patients with non‐small cell lung cancer (NSCLC) harboring epidermal growth factor receptor ( EGFR ) T790M mutation between the generation of prior EGFR tyrosine kinase inhibitors (TKIs). Methods: We retrospectively reviewed clinical data from the medical records of consecutive patients with advanced NSCLC who had developed resistance to first‐ or second‐generation EGFR‐TKIs due to EGFR T790M mutation and were subsequently treated with osimertinib at Juntendo University Hospital. In patients with available tumor samples, target amplicon sequencing analyses were performed to explore the genetic biomarkers. Results: A total of 38 patients with NSCLC harboring EGFR T790M mutation were treated with osimertinib. Eight patients were classified into group A (afatinib followed by osimertinib) and 30 patients were classified into group B (first‐generation EGFR‐TKI followed by osimertinib). Progression‐free survival (PFS) was significantly longer in group A than in group B (median PFS; not reached vs. 11.0 months, P = 0.018). Fourteen patients had available tissue samples collected before osimertinib treatment for target sequencing. In group A we found no additional mutations, other than EGFR T790M mutation. On the other hand, there were three samples in which other mutations emerged, in addition to EGFR T790M mutation, in group B. Conclusions: PFS of osimertinib was significantly longer in patients with NSCLC harboring EGFR T790M mutation after treatment with afatinib than in patients after treatment with first generation EGFR‐TKIs. Additional mutations other than EGFR T790M may affect the efficacy of osimertinib treatment. Key points: Significant findings of the study: PFS of osimertinib was significantly longer in patients with NSCLC harboring EGFR T790M mutation after treatment with afatinib than in patients after treatment with first generation EGFR‐TKIs. What this study adds: Additional mutations other than EGFR T790M may affect the efficacy of osimertinib treatment. Abstract : There are few studies that directly compare the difference between the generation of prior EGFR tyrosine kinase inhibitors (TKIs) before osimertinib treatment in patients with non‐small cell lung cancer (NSCLC) harboring epidermal growth factor receptor ( EGFR ) T790M mutation. In our retrospective study, progression‐free survival of osimertinib was significantly longer in patients with NSCLC harboring EGFR T790M mutation after treatment with afatinib than in patients after treatment with first generation EGFR‐TKIs.